2011
DOI: 10.1007/s10897-011-9382-9
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Ethical and Professional Challenges Experienced by Spanish Health‐Care Professionals that Provide Genetic Counseling Services

Abstract: Genetic testing is increasingly applied for diagnosis and clinical treatment. In some countries, genetic counseling services are provided by professionals with specific training in this discipline, whereas other countries have no teaching programs and counseling is offered by physicians, nurses, pharmacists or biochemists. This counseling raises more and more ethical dilemmas for health professionals at their clinics. The purpose of this study was to analyze the characteristics of Spanish professionals devoted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 14 publications
3
32
1
Order By: Relevance
“…28 Australian genetic counselors were found to use 8 of the 11 strategies referred to, 27 and Spanish genetic counselors were found to use 10 of the strategies and one additional strategy-"study of the family group. " 26 The finding of this study, that genetic health professionals commonly seek advice from their peers, contrasts with the survey of genetic counselors in Australia, which found that only a small proportion of genetic counselors (15.4%) would recommend discussion with other health professionals. 27 Although these previous surveys have provided some information about strategies for managing ethical dilemmas, they posed only hypothetical questions, asking respondents what they would advise a colleague to do when encountering an ethical dilemma but not what they do, or have done, in their own practice.…”
Section: Comparisons With Other Studiescontrasting
confidence: 83%
See 2 more Smart Citations
“…28 Australian genetic counselors were found to use 8 of the 11 strategies referred to, 27 and Spanish genetic counselors were found to use 10 of the strategies and one additional strategy-"study of the family group. " 26 The finding of this study, that genetic health professionals commonly seek advice from their peers, contrasts with the survey of genetic counselors in Australia, which found that only a small proportion of genetic counselors (15.4%) would recommend discussion with other health professionals. 27 Although these previous surveys have provided some information about strategies for managing ethical dilemmas, they posed only hypothetical questions, asking respondents what they would advise a colleague to do when encountering an ethical dilemma but not what they do, or have done, in their own practice.…”
Section: Comparisons With Other Studiescontrasting
confidence: 83%
“…Also, no definition of these terms was given to respondents in these studies, and therefore respondents' interpretation of the terms "frequent" and "not frequent" might have varied. [26][27][28] Clarke and colleagues 14 used a prospective study design to document 65 instances of nondisclosure of genetic status to at-risk relatives over a 12-month period in the United Kingdom and in two Australian centers. However, nondisclosure was the only ethical dilemma related to genetic testing that was included in that study.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the respondents in the Spanish study (Abad-Perotín et al 2012) and less than four per cent in Australia (Alliman et al 2009) and the USA (Bower et al 2002) indicated that they frequently face challenges due to value conflicts. The situation in Austria is similar (Gschmeidler and Flatscher-Thoeni 2013).…”
Section: Values and Health Carementioning
confidence: 93%
“…Values have been studied in regard to the situation of health professionals and to their influence on the doctor-patient relationship. Bernhardt et al (2010) focussed on distressing experiences of clinical geneticists, genetic counsellors and genetic nurses and noticed value (Bower et al 2002;Alliman et al 2009;Abad-Perotín et al 2012;Gschmeidler and Flatscher-Thoeni 2013;Groepper et al 2014). …”
Section: Values and Health Carementioning
confidence: 99%